Implementasi Filosofi “Menumbuhkan Padi” sebagai Media Pembentukan Kepemimpinan Siswa dalam Perspektif Ki Hajar Dewantara di SMP Negri 1 Jalaksana Kabupaten Kuningan - Sauqi, Achmad; Yasin, Ahmad Alamuddin (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2025)
This study aims to describe the implementation of the “growing rice” philosophy in shaping student leadership character at SMP Negeri 1 Jalaksana. This concept refers to the thoughts of Ki Hajar Dewantara, who emphasized education as an effort to guide students’ natural potential to develop holistically, encompassing cognitive, affective, and psychomotor aspects. The research employed a qualitative method with an ethnographic approach conducted over one week, involving observations and in-depth interviews with the principal, teachers, and students. Primary data were obtained from observations and interviews, while secondary data were derived from relevant literature, including books and scholarly articles. The findings reveal that the implementation of the “growing rice” philosophy is carried out in three stages: pre-growing, during growth, and post-growing. At the pre-growing stage, teachers prepared learning strategies aligned with the Merdeka Curriculum, including project-based learning, differentiated instruction, socio-emotional competency development, reflective practices, and positive discipline. During the growth stage, activities were conducted through intracurricular, extracurricular, and co-curricular programs that provided students with opportunities to create, collaborate, and participate in decision-making. The post-growing stage encompassed “harvesting,” reflected in the enhancement of students’ leadership skills such as effective communication, teamwork, conflict management, and decision-making, along with semester-based evaluations to monitor the development of leadership character. In conclusion, the implementation of the “growing rice” philosophy fosters students’ leadership character, creating an inclusive, cooperative, and positive school culture. Thus, Ki Hajar Dewantara’s educational philosophy remains relevant in supporting the goals of the Merdeka Curriculum to shape a generation that is intelligent, of strong character, and prepared to face future challenges.